Percutaneous transcatheter bariatric embolotherapy for weight loss in obesity: two year data from a prospective RCT. (25th November 2020) - Reddy, V.Y; Fried, M; Neuzil, P; Rosen, R; Sramkova, P; Kipshidze, N; Kipshidze, N
Abstract: Background/Introduction: Obesity is an important risk factor associated with poor cardiovascular and metabolic outcomes. Dietary, medical, and surgical weight loss strategies are often unsuccessful, unsustainable or accompanied by risks. Pre-clinical and early case series reported that transcatheter bariatric embolotherapy (TBE) of the left gastric artery reduces weight, by reducing "hunger" hormones from the gastric fundus. We studied TBE in a double-blind, sham procedure, first in human RCT of patients (pts) with obesity, and following completion of the initial study we asked subjects to return after 2 years post-embolization for further evaluation. Purpose: The purpose of this extension study was to assess the long-term weight loss and other outcomes in subjects who underwent TBE for weight loss. Methods: In the initial RCT subjects were randomized 1:1 to either a Sham (skin nick & 1 hr wait) or TBE following IV Propofol sedation. All pts received Lifestyle Therapy (behavioral and diet education); these staff following the pts were also blinded to treatment. Subjects completed the initial study when reaching the 1 year-follow-up visit. Subjects were then invited to return to the weight loss clinic at 2 years post-embolization for further evaluation on weight loss, blood pressure, pre-diabetic clinical status, satiety, and quality of life. Results: A total of 44 pts (age 45.5±9.8; 36/8 M/F; BMI 39.6±3.8) were enrolled, of which 40 pts were randomized equally to groups, with no major complications. Mild, transient epigastric pain was seen, but EGDs showed no major abnormalities. Weight loss was improved with TBE by 6 mo, and maintained over the full 12 mo by both intention-to-treat and per-protocol analyses. At 2 years post-embolization, subjects treated with TBE demonstrated a mean 9% TBWL and 25% EBWL. Conclusion(s): Bariatric embolization is safe and when used along with lifestyle therapy, results in clinically significant weight loss. Long-term data demonstrates evidence that subjects treated with TBE continue to maintain their weight loss up to 2 years post-treatment. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Endobar Solutions LLC